Upaya Meningkatkan Kedisiplinan Siswa Menggunakan Model Paradigma Pedagogi Reflektif pada Siswa Kelas III 0107 Tanjung Botung - Irma Sari Daulay; Amril Saputra Nst; Esma Saskia Siregar; Lukmanul Hakim Dalimunthe; Marito Marito; Nabila Hasanah; Saskia Rahmadani Nasution (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Student discipline is one of the important factors in supporting the success of the learning process in elementary schools. However, in reality, there is still a low level of student discipline, particularly in terms of punctuality, compliance with rules, and responsibility in completing assignments. This study aims to improve student discipline through the application of the Reflective Pedagogy Paradigm model to third-grade students at SDN 0107 Tanjung Botung. The research method used was Classroom Action Research (CAR), which was carried out in two cycles, with each cycle covering the stages of planning, implementation, observation, and reflection. Data collection techniques were carried out through observation, interviews, and documentation. The results showed that the application of the Reflective Pedagogy Paradigm model was able to significantly improve student discipline, as seen from the increase in punctuality, compliance with school rules, and student responsibility in completing tasks. Based on these results, it can be concluded that the Reflective Pedagogy Paradigm model is effective as an alternative learning strategy to foster and improve student discipline in elementary schools.